2022
DOI: 10.1021/acsomega.1c07276
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Experiment on NOx Reduction by Urea Solution Injection in the Fuel-Rich Zone of a 330 MW Tangentially Pulverized Coal-Fired Boiler

Abstract: The effects of various factors on NO x reduction by urea solution injection in the fuel-rich zone (UIFR) under a reducing atmosphere at high temperature were experimentally investigated in a 330 MW tangentially pulverized coal-fired boiler. The experimental results indicated that the NO x emission of the boiler could be effectively reduced by using the UIFR method, and the NO x reduction efficiency was mostly affected by the opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The urea solution with a mass concentration of 10% was selected as the reducing agent, and the total flow rate of the reducing agent should be 0.0374 kg/s and NSR = 1. Numerous studies have shown that the NSR between 0.5 and 2 is more appropriate, ,, and the denitrification efficiency is lower for too small an ammonia-to-nitrogen ratio, and the ammonia escape rate increases significantly for too large an ammonia-to-nitrogen ratio. Therefore, in this experiment, the NSR was selected as 0.5, 0.75, 1, 1.25, 1.5, 1.75, and 2 gradient flow rates of reductant injection to investigate the effect of injection volume on reduction efficiency and ammonia escape.…”
Section: Resultsmentioning
confidence: 99%
“…The urea solution with a mass concentration of 10% was selected as the reducing agent, and the total flow rate of the reducing agent should be 0.0374 kg/s and NSR = 1. Numerous studies have shown that the NSR between 0.5 and 2 is more appropriate, ,, and the denitrification efficiency is lower for too small an ammonia-to-nitrogen ratio, and the ammonia escape rate increases significantly for too large an ammonia-to-nitrogen ratio. Therefore, in this experiment, the NSR was selected as 0.5, 0.75, 1, 1.25, 1.5, 1.75, and 2 gradient flow rates of reductant injection to investigate the effect of injection volume on reduction efficiency and ammonia escape.…”
Section: Resultsmentioning
confidence: 99%
“…NO x emissions are a global problem, and flue gases emitted from various industrial processes seriously pollute the environment. 1,2 With China's improved flue gas emission standards 3,4 and the strengthening of air pollution regulations, 3 the focus of NO x treatment has shifted to non-electric industries, mainly the steel, cement, and coking industries. The requirements for the denitration of boiler exhaust gases in various industries are becoming increasingly stringent.…”
Section: Introductionmentioning
confidence: 99%